2022
DOI: 10.1093/ofid/ofac028
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Use of Tedizolid Phosphate for 28 Days or More: A Case Series Describing Tolerability and Clinical Success

Abstract: Tedizolid has activity against Gram-positive pathogens as well as Mycobacterium spp and Nocardia spp. Real-world evidence supporting long-term tolerability and clinical success of tedizolid is lacking. Prolonged tedizolid therapy (median, 188 days; interquartile range, 62–493 days) appeared to be well tolerated in 37 patients (8.1% experienced adverse effect leading to discontinuation). Clinical success was 81.3% in those evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Our findings are similar to that of Morisette et al, who retrospectively looked at safety of prolonged tedizolid in 37 subjects who took tedizolid for a mean of 188 days ( 18 ), compared to our median of 96 days. In their study, they similarly found no new clinically significant hematologic cytopenias or neuropathies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are similar to that of Morisette et al, who retrospectively looked at safety of prolonged tedizolid in 37 subjects who took tedizolid for a mean of 188 days ( 18 ), compared to our median of 96 days. In their study, they similarly found no new clinically significant hematologic cytopenias or neuropathies.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of efficacy, we found a treatment failure rate of 11%, similar to the rates of 6%–24% reported by others ( 18 20 , 23 ). How these treatment failure rates compare to that of other antimicrobial regimens, intravenous or oral, is unclear.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Two case reports describe successful tedizolid use for NTM infection in patients with previous linezolid-induced cytopenia [ 72 , 73 ]. Tedizolid has greater antibacterial potency, better pharmacokinetic/pharmacodynamic profiles, and lower hematologic and neurologic toxicity than does linezolid [ 74 , 75 ]. The relatively weak monoamine oxidase inhibition and poor central nervous system penetration of tedizolid may also lead to fewer drug interactions with serotonergic agents [ 76 , 77 ].…”
Section: Emerging Treatmentsmentioning
confidence: 99%